Positivity of chromatic symmetric functions associated with Hessenberg functions of bounce number 3 - Cho, Soojin; Hong, Jaehyun (Electronic Journal of Combinatorics, 2022)
We give a proof of the Stanley-Stembridge conjecture on chromatic symmetric functions for the class of all unit interval graphs with independence number 3. That is, we show that the chromatic symmetric function of the incomparability graph of a unit interval order in which the length of a chain is at most 3 is positively expanded as a linear sum of elementary symmetric functions.